Full-Cycle Rehabilitation Therapy of Coronary Heart Disease in the Elderly - DONG Anqin (康复学报)
Coronary atherosclerotic heart disease (CHD) is one of the main causes affecting the health of elderly people (≥65 years old). CHD is a threat to the life and health of the elderly, and also brings a huge economic burden to families and society. Because the elderly often have the underlying diseases such as hypertension, diabetes, hyperlipemia, and so on, which seriously affects the occurrence and progression of CHD, the prevention and treatment of CHD in the elderly is facing a huge challenge. In recent years, scholars dedicate on the study of full-cycle rehabilitation management of CHD in the Elderly, in order to reduce the recurrence rate of cardiovascular events and prolong life span. The emergence of cardiac rehabilitation plays an important role in the transformation of CHD from treatment to prevention, which is conducive to halting the progression of CHD, improving the mental state and psychological pressure of patients, and accelerating the recovery of activities of daily living. Therefore, this paper will focus on disease-centered rehabilitation management for the elderly in the whole cycle, aiming to provide scientific guidance for the safety and effectiveness of CHD in the elderly, and promote the development of full-cycle rehabilitation for the elderly with CHD in China.